Diplomasi Budaya Indonesia Dalam Mempromosikan Pencak Silat Melalui USA Pencak Silat Open Tournament di Amerika Serikat - Karlina, Lilis; Daud Yusuf, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the role of cultural diplomacy in promoting martial arts as an intangible cultural heritage of Indonesia through the USA Martial Arts Open Tournament event in the United States. Using a qualitative approach involving interview, observation, and documentation methods, this study found that the tournament served not only as a sporting event, but also as an effective means of cultural diplomacy to introduce Indonesian cultural values and identity to the international community. The results of the study show that although martial arts climbers face various challenges, such as lack of popularity and infrastructure, this activity contributes to the improvement of Indonesia’s image on the global stage, in accordance with the constructivism theory. This study emphasizes the importance of a sustainable cultural diplomacy strategy in promoting traditional martial arts at the international level.